Non-Clinic Blood Pressure Measurement – More Light, Less Darkness - Kapur, Vinay (Asian Journal of Medical Sciences, 2018)
Non-clinic blood pressure measurements are very important in confirming diagnosis of hypertension and they give us an idea of associated cardiovascular risk more precisely than clinic BP measurements. It can detect masked hypertension and white coat hypertension & ABPM especially can monitor night-time BP diagnosing individuals with nocturnal hypertension. Masked hypertension and nocturnal hypertension are strongly related with target organ damage along with enhanced morbidity and mortality due to cardiovascular causes. ABPM can also measure early morning rise of BP, mean 24 hour BP, diurnal variation as well as average real variability. Home BP monitoring by patients themselves leads to their greater involvement in maintaining BP records and in achieving treatment goals. The purpose of this review is to preferentially discuss role of non-clinic BP monitoring in making accurate diagnosis and deciding treatment of hypertension that might help a great deal in reducing morbidity and mortality associated with it. Asian Journal of Medical Sciences Vol.10(1) 2019 13-18